2019
DOI: 10.1093/abbs/gmz009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toll-like receptor 2 antibody inhibits nuclear factor kappa B activation and attenuates cardiac damage in high-fat-feeding rats

Abstract: Long-time consumption of high-fat food is a direct cause of cardiovascular diseases, and high-fat-related inflammation plays an important role in it. Toll-like receptors (TLRs), especially TLR2 and TLR4, play important roles in high-fat-related inflammation. However, the impact of TLR2 on high-fat-associated cardiovascular complications is still unknown. In this study, we try to investigate the relationship between TLR2 and high-fat-related cardiac injury. SD rats were allocated to either a control group which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…They play a significant role in myocardial inflammation as they activate the expression of several pro-inflammatory cytokine genes ( Vaure and Liu, 2014 ). They are bound to the MyD88 (adapter molecule), on activating NF-κB ( Wang et al, 2019b , Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…They play a significant role in myocardial inflammation as they activate the expression of several pro-inflammatory cytokine genes ( Vaure and Liu, 2014 ). They are bound to the MyD88 (adapter molecule), on activating NF-κB ( Wang et al, 2019b , Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has confirmed this ( Peterson et al, 2018 ). Wang W. Z. et al (2019b )found that anti-TLR2 antibody inhibits NF-κB activation and reduces cardiac damage in high-fat-feeding rats. Our study also confirmed that TLR2 regulated the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that after stimulation, the intracellular signaling cascade causes the release of NF-κB dimer, and NF-κB dimer is further activated by various post-translational modifications and transferred to the nucleus, where it binds to the target gene and become acetylated to initiate the transcription of the target gene. 35,36 It is known that JNK/SAPKs are associated with metabolism, motility, apoptosis and proliferation; when stimulated, some activated JNK transfers into the nucleus to regulate a variety of transcription factors, such as c-Jun, activator protein 1 (AP-1) and p53. 37 In this study, the IF staining results showed that GroEL treatment accelerated the nuclear accumulation of p-JNK and total NF-κB in hPDLSCs, and the level of acetylated NF-κB in the nucleus increased.…”
Section: Discussionmentioning
confidence: 99%